Corpus-driven Bantu Lexicography Part 3: Mapping Meaning onto Use in Lusoga - de Schryver, Gilles-Maurice; Nabirye, Minah (Lexikos, 2018)
This article is the third instalment in a trilogy of studies that deal with corpus-driven Bantu lexicography as applied to Lusoga. Having dealt with corpus-building in Part 1, and macrostructural aspects in Part 2, we now focus on the microstructure of a dictionary and in particular on the concept of Mapping Meaning onto Use. The starting point is Patrick Hanks's book chapter by the same title, which we transpose to a study of the high-frequent motion verb -v- in Lusoga. Our detailed analysis is as much practical as it is methodological.